(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background: Short fiber reinforced resin composite (Ever X Posterior) is a bulk fill resin composite indicated as a core dentine substitute at high stress-bearing areas improve strength and fracture toughness of conventional resin composite and restored teeth. So, this randomized clinical trial was conducted to validate clinical performance of short fiber reinforced resin composite in endodontically treated molars. Method: 56 participants having endodontically treated lower molars with moderate amount of remaining tooth structure were randomly enrolled in this trial and received either Ever X Posterior covered by Gaenial posterior or only Gaenial posterior resin composite that applied according to manufacturer instructions. Mann-Whitney U test was used for intergroup comparisons and Wilcoxon signed rank test was used for intragroup comparisons. The significance level was set at p ? 0.05. No statistically significant difference was observed between both tested groups for all USPHS criteria at different follow-up periods except for color match favoring Gaenial posterior with a significant difference between both groups. Conclusion: Both types of restorations showed an acceptable clinical performance along 1 year follow-up period.